1995
DOI: 10.3719/weed.40.104
|View full text |Cite
|
Sign up to set email alerts
|

Differential Growth Response of Rice Cultivars to Pyrazosulfuron-ethyl.

Abstract: In growth response to pyrazosulf uron-ethyl [ethyl 5-[[3-(4, 6-dimethoxypyrimidin-2-yl) ureido] sulf onyl]-1 H-1-methylpyrazole-4-carboxylate], indica rice cultivars were more tolerant than japonica cultivars in a manner similar to bensulfuronmethyl [methyl a-[[3-(4, 6-dimethoxypyrimidin-2-yl) ureido] sulf onyl]-o-toluate]. The growth inhibition by pyrazosulf uronethyl and bensulfuron-metyl was reduced by dimepiperate[S-(a, a-dimethylbenzyl) piperidine-l-carbothioate] in indica and japonica rice cultivars but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…BS; Zhang et al, 2002;Pan et al, 2006;Wang et al, 2012). It was also reported that japonica rice varieties Kamenoo-4 and Joshu tended to be more sensitive to BSM than indica rice varieties IR-8 and IR-26 (Kobayashi et al, 1995), suggesting the possibility that, in addition to the CYP81A6 gene, the CYP72A31 gene is involved in BSM tolerance. To check whether the CYP72A31 gene confers BSM tolerance, the BSM sensitivity in CYP72A31-overexpressing Arabidopsis was checked.…”
Section: Comparison Of Als-inhibiting Herbicide Tolerance By Cyp72a31mentioning
confidence: 99%
“…BS; Zhang et al, 2002;Pan et al, 2006;Wang et al, 2012). It was also reported that japonica rice varieties Kamenoo-4 and Joshu tended to be more sensitive to BSM than indica rice varieties IR-8 and IR-26 (Kobayashi et al, 1995), suggesting the possibility that, in addition to the CYP81A6 gene, the CYP72A31 gene is involved in BSM tolerance. To check whether the CYP72A31 gene confers BSM tolerance, the BSM sensitivity in CYP72A31-overexpressing Arabidopsis was checked.…”
Section: Comparison Of Als-inhibiting Herbicide Tolerance By Cyp72a31mentioning
confidence: 99%
“…The low phytotoxicity, long medicinal effect period, and low mobility of dimepiperate were first reported by Japan’s Mitsubishi Chemical Co., Ltd. in 1976, and it was used as a highly selective herbicide to control weeds in crops, such as rice. In 1986, dimepiperate was reported to alleviate the phytotoxicity of the sulfonylurea herbicide bensulfuron in paddy fields. , Piperazine was used as the starting material, and dimepiperate was directly obtained by a one-step condensation reaction (Scheme ).…”
Section: Synthesis Of Commerical Herbicide Safenersmentioning
confidence: 99%
“…In 1986, dimepiperate was reported to alleviate the phytotoxicity of the sulfonylurea herbicide bensulfuron in paddy fields. 56,57 Piperazine was used as the starting material, and dimepiperate was directly obtained by a one-step condensation reaction (Scheme 8). 58 ■ DESIGN OF NOVEL HERBICIDE SAFENERS IN RECENT YEARS Sulfonamide Herbicide Safeners.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, a wide range of herbicide susceptibility exists in cultivated rice, e.g. indica vs. japonica to acetolactate synthase (ALS) inhibitors (Kobayashi, Yogo and Sugiyama, 1995), and whether having functional his1 gene which confers resistance to 4-HPPD inhibitors (Maeda et al, 2019). Moreover, herbicide-resistant rice cultivars are more frequently used as one of the management options in the United States and Latin America (Sudianto et al, 2013).…”
Section: Agronomic and Other Intensively Managed Ecosystems Where The...mentioning
confidence: 99%